A Convenient and Robust Test to Quantify Interocular Suppression for Children With Amblyopia. (July 2019) - Chen, Hui; He, Zhifen; Xu, Jinling; Mao, Yu; Liang, Yunjie; Lin, Danli; Xu, Meiping; Dai, Zhiyue; Chen, Xiaoxin; Zhou, Jiawei; Yu, Xinping
Interocular suppression was quantified by the interocular luminance difference that was needed when the two eyes were balanced in discriminating a black–white stripe formed butterfly stimulus, which was dichoptically presented through polarized glasses. Stronger interocular suppression was found in amblyopes than that in controls at both the near (33 cm, 0.95 ± 1.00 vs. 0.14 ± 0.18, p  < .001) and far (5 m, 2.18 ± 0.97 vs. 0.24 ± 0.16, p  < .001) viewing distances. The interocular suppression in amblyopes was significantly correlated with the interocular visual acuity difference, the visual acuity of amblyopic eye, the Worth-4-Dot test, and the stereo acuity at both the near and far distances (for all cases, p  < .001). Our new test enables convenient and robust measurements of interocular suppression in children with amblyopia. The measured interocular suppression is in agreement with other clinical measures.